Análise de fadiga de turbinas eólicas offshore tipo monopile com conexão grauteada - Gomes, Fellipe Araujo (2019)
One of the critical regions of an Offshore Wind Turbine (OWT) is the structural connection between the superstructure and its foundation. This connection is commonly peformed through a metal cylindrical joint filled with high strength concrete, made by the overlapping of a metal transition piece, which transfers the stresses to the foundation through the grout. In this work, the fatigue damage of a monopile foundation based on cohesive and non-cohesive soils is evaluated using the SIMA-RIFLEX software and focusing on the connection region. The soil-structure interaction is simulated applying p-y curves proposed by ANSI/API-RP-2GEO (2011) and DNVGL-ST-0126 (2016). Fatigue damage is analyzed in different regions of the monopile and grout evaluating two types of connections: conical and tubular with shear key. Moreover, in these analyzes, different types of soil and environmental conditions similar to the Brazilian coast were considered. In the grouted connection, it was observed that the mean stress and the number of shear keys influence the capacity of the grout, with greater damages present in the conical connections. The critical region of the monopile in sandy soils was identified 6.5 m below the seabed, regardless the angle of friction. For cohesive soils, the critical region varied between 6.5 and 18.5 m below the seabed depending on the undrained resistance value. For both grout and welded joints, the greatest damage occurs in the non-operational situation, due to the absence of aerodynamic damping, being more noticeable in clayey soils with undrained resistance equal to 10 kPa.